EVALUATION OF ONLINE AND OFFLINE LEARNING USING STAD METHOD IN BASIC ACCOUNTING COURSES (CASE STUDY OF CLASS X ACCOUNTING SMK BOEDI OETOMO 3 MAOS) - Tanty, Dai Hansus (Al'Adzkiya Journal, 2021)
The purpose of this study was to evaluate student learning outcomes during online and offline learning. The approach used in this study is a descriptive-qualitative approach. This approach is to describe the implementation of learning during the Covid-19 period at SMK Boedi Oetomo 3 Maos class X majoring in Accounting and Institutional Finance as many as 30 students in basic accounting subjects. The source of the data comes from the value of students in offline and online learning and the results of observations. The results showed that the learning outcomes of students in offline learning were better than the learning outcomes of students in online learning. The data shows the average offline learning class using the STAD method is 80.23 with the number of students scoring below the KKM is 9 children (30%). While the average online learning class is 67.1 with the number of student scores below the KKM is 20 children (67%).